Strategies for Sustainable Sea Cucumber Farming in Jaffna - Thakshayini, S.; Christian, M.D.A. (Faculty of Arts University of Jaffna, Sri Lanka, 2025)
The study addresses the growing importance of aquaculture in the region and the need for sustainable practices in this emerging sector. The main objective is to identify effective strategies for the sustainable development of sea cucumber farming in the Jaffna district. A mixed-methods approach was employed, combining field research, interviews, questionnaires, and group discussions for primary data collection, while secondary sources were also consulted. Quantitative data were systematically presented and analyzed using descriptive statistical tools in SPSS (version 21), complemented by qualitative insights from farmers. The analysis shows that 85.1% of farmers are engaged due to high income opportunities, while 95.7% reported limited government support and 59.6% viewed climate conditions as neutral. Key problems identified include climate risks, theft, and private dominance, whereas strengths include income generation, foreign exchange earnings, and employment opportunities. Weaknesses such as environmental degradation and resistance from small-scale fishermen, and challenges such as high investment costs, unstable weather, and institutional inattention, were also highlighted. The findings reveals that sustainable sea cucumber farming requires stronger government involvement, expansion of training workshops, adoption of climate adaptation measures, enhanced security against theft, and promotion of value-added products for export. These strategies provide a pathway to ensure sea cucumber farming in Jaffna which could evolve as an economically viable, environmentally responsible, and socially inclusive industry.
Keywords: Environmental degradation; Jaffna; Sea cucumber; Sustainable development